Preliminary - Gómez Botero, Maryory Astrid (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
Revista Facultad de Ingeniería published its first issue in 1984, as the materialization of the efforts of many professors, especially from the School of Engineering. In tribute to those leaders and visionaries, who believed and made this dream possible, I’d like to remember the first members of the Editorial Board. Dr. Germán Urrego was the Dean in turn, Dr. Oscar Piedrahíta, the Journal Editor, Dr. Gildardo Hernández, the Deputy Director, and Dr. Rodrigo Peñaloza, the representative of the research centers.